Explaining the Growth of Part-Time Employment : Factors of Supply and Demand - Maurice Hogerbrugge; Rob Euwals (Institute for the Study of Labor (IZA), 2004)
Using the Dutch Labour Force Survey 1991-2001, the authors investigate the incidence of part-time employment in the country with the highest part-time employment rate of the OECD countries. Women fulfil most part-time jobs, but nevertheless a considerable fraction of men works part-time as well. Evidence from descriptive statistics and a macro-econometric model at the sectoral level of industry suggests that the growth of part-time employment in the 1990s relates strongly to the growth in female labour force participation. Factors of labour demand, like the shift from manufacturing to services, turn out to play a significant role as well.
Keywords: J23; J21; C33; 330; labour demand; labour supply; part-time employment; panel data; Teilzeitarbeit; Frauenerwerbstätigkeit; Arbeitsangebot; Drei-Sektoren-Hypothese; Schätzung; Niederlande